Revolutionizing Supply Chain Management with AI Agents on DataBricks - Pritam Roy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of artificial intelligence in supply chain management has revolutionized traditional operations through advanced automation and intelligent decision-making capabilities. The DataBricks platform enables the deployment of specialized AI agents - Procurement Policy Advisor, Quality Inspection Advisor, Sustainability Policy Advisor, and Goods Delivery Advisor - each addressing specific operational challenges while delivering measurable benefits. These agents leverage machine learning algorithms and predictive analytics to enhance procurement processes, quality control, sustainability reporting, and logistics operations. The implementation has significantly improved operational efficiency, cost reduction, and process optimization across diverse supply chain functions. The framework’s modular architecture facilitates emerging technologies’ continuous evolution and integration, positioning organizations for enhanced competitiveness in dynamic market environments.